The Relationship of Throwing Arm Mechanics and Elbow Varus Torque: Within-Subject Variation for Professional Baseball Pitchers Across 82,000 Throws - Camp, Christopher L; Tubbs, Travis G; Fleisig, Glenn S; Dines, Joshua S; Dines, David M; Altchek, David W; Dowling, Brittany (The American journal of sports medicine, 2017)
Likely due to the high level of strain exerted across the elbow during the throwing motion, elbow injuries are on the rise in baseball. To identify at-risk athletes and guide postinjury return-to-throw programs, a better understanding of the variables that influence elbow varus torque is desired. To describe the within-subject relationship between elbow varus torque and arm slot and arm rotation in professional baseball pitchers. Descriptive laboratory study. A total of 81 professional pitchers performed 82,000 throws while wearing a motusBASEBALL sensor and sleeve. These throws represented a combination of throw types, such as warm-up/catch, structured long-toss, bullpen throwing from a mound, and live game activity. Variables recorded for each throw included arm slot (angle of the forearm relative to the ground at ball release), arm speed (maximal rotational velocity of the forearm), arm rotation (maximal external rotation of the throwing arm relative to the ground), and elbow varus torque. Linear mixed-effects models and likelihood ratio tests were used to estimate the relationship between elbow varus torque and arm slot, arm speed, and arm rotation within individual pitchers. All 3 metrics-arm slot (χ = 428, P < .001), arm speed (χ = 57,683, P < .001), and arm rotation (χ = 1392, P < .001)-were found to have a significant relationship with elbow varus torque. Within individual athletes, a 1-N.m increase in elbow varus torque was associated with a 13° decrease in arm slot, a 116 deg/s increase in arm speed, and an 8° increase in arm rotation. Elbow varus torque increased significantly as pitchers increased their arm rotation during the arm cocking phase, increased the rotational velocity of their arm during the arm acceleration phase of throwing, and decreased arm slot at ball release. Thus, shoulder flexibility, arm speed, and elbow varus torque (and likely injury risk) are interrelated and should be considered collectively when treating pitchers. It is well established that elbow varus torque is related to ulnar collateral ligament injuries in overhead throwers. This study describes the relationship of arm slot, arm speed, and arm rotation to elbow varus torque in an attempt to identify modifiable risk factors for injury.